Perceived stress is associated with a higher symptom burden in cancer survivors. Issue 24 (10th September 2019) - Mazor, Melissa; Paul, Steven M.; Chesney, Margaret A.; Chen, Lee‐May; Smoot, Betty; Topp, Kimberly; Conley, Yvette P.; Levine, Jon D.; Miaskowski, Christine
Abstract : Background: Although multiple co‐occurring symptoms are a significant problem for cancer survivors, to the authors' knowledge little is known regarding the phenotypic characteristics associated with a higher symptom burden. The objectives of the current study were to evaluate the occurrence, severity, and distress associated with 32 symptoms and examine the phenotypic and stress characteristics associated with a higher symptom burden. Methods: A total of 623 cancer survivors completed a demographic questionnaire, as well as measures of functional status, comorbidity, and global (Perceived Stress Scale) and cancer‐related (Impact of Event Scale–Revised) stress. The Memorial Symptom Assessment Scale was used to evaluate symptom burden. Multiple linear regression analysis was used to determine the phenotypic characteristics associated with a higher symptom burden. Results: The mean number of symptoms was 9.1 (±5.2). The most common, severe, and distressing symptoms were lack of energy, problems with sexual interest/activity, and hair loss, respectively. Poorer functional status, a higher level of comorbidity, and a history of smoking as well as higher Perceived Stress Scale and Impact of Event Scale–Revised scores were associated with a higher symptom burden. The overall model explained approximately 45.6% of the variance in symptom burden. Conclusions: Although cancer survivors report a high number of co‐occurring symptoms of moderate severity and distress, in the current study, no disease or treatment characteristics were found to be associated with a higher symptom burden. Clinicians need to assess for general and disease‐specific stressors and provide referrals for stress management interventions. Future studies need to examine the longitudinal relationships among symptom burden, functional status, and level of comorbidity, as well as the mechanisms that underlie the associations between stress and symptom burden. Abstract : Cancer survivors report a high number of co‐occurring symptoms of moderate to severe intensity. Both general and disease‐specific stressors are associated with a higher symptom burden.